An Economic Analysis of Cointegration for Potato Market in Tamil Nadu, India - Vigila, V.; Shivakumar, K. M.; Rohini, A.; Sivakami, B. (Insights into Economics and Management Vol. 7, 2021)
The present study aimed to analyze the potato market integration in India, specifically how the Tamil Nadu market behaves with respect to the behavior of other potato markets across India. Major potato markets, such as Madhya Pradesh, Uttar Pradesh and Gujarat, which have a majority share in the total supply potato to Tamil Nadu were selected for market integration analysis. Since price data for Tamil Nadu market was non-stationary and other market prices were stationary in level form, Autoregressive Distributed Lag Model (ARDL) was used to estimate cointegration (long run equilibrium) among these markets. Month wise potato price data from January 2005 to September 2016 were collected from different sources and used for analysis. Results revealed that long run equilibrium existed among the potato markets in Tamil Nadu, Madhya Pradesh, Uttar Pradesh and Gujarat but the speed of adjustment of equilibrium level is very less in the long run. Change in the potato price of Gujarat market was the key determinant of shocks in the potato market of Tamil Nadu.